Static Analysis and Experimental Validation of Containerized Fire Pump Stations - Firmansah; Adyana; T. Ardiansyah (Riviera Publishing, 2026)
Containerized fire pump stations repurpose ISO 40ft High Cube containers but require large openings for ventilation and access, altering structural stiffness. his study evaluates a modified container under three load cases: LC2 (dynamic lifting, 1.2g), LC3 (static operation), and LC4 (2-tier stacking, 1.8g). A mesh convergence study established a reference mesh with maximum element size h = 20 mm. Validation was performed by comparing incremental deflections at six measurement points (T1–T6) between FEA and a workshop static test under LC3, using Mean Absolute Percentage Error (MAPE) as the accuracy metric. The validated model achieved a global MAPE (T1–T4) of 10.01%, indicating adequate agreement in global stiffness. For the reference mesh, key results are: LC3 – ovm,max = 161.56 MPa, omax = 2.69 mm, SFdesign,min = 1.55; LC2 – ovm,max = 236.71 MPa, omax = 3.40 mm, SFdesign,min = 1.14; LC4 – ovm,max = 296.21 MPa, omax = 2.86 mm, SFdesign,min = 1.16. Stress hotspots are localized around openings, showing indications of spot stress/singularity; therefore, structural interpretation focuses on global response and nominal stresses in primary load-carrying members. The integration of NFPA 20 ventilation and access requirements with ISO 1496-1-based structural assessment is feasible using a validated FEA model. The modified container meets yield and deflection limits, providing defensible operational limits for lifting and 2-tier stacking under controlled dynamic factors.